(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Pregnancy causes many endocrine and physiological changes in respond to stimuli caused by the fetus and its adnexa. During pregnancy, if you suffer from prenatal coagulation disorder, it can cause death for both mother and fetus. Detecting disorders of blood coagulation indices in the prenatal period helps monitor pregnancy and promptly handle abnormalities, creating conditions for both mother and fetus to develop healthily and safely. Therefore, learning about disorders of coagulation and hemostasis indices in the prenatal period will help clinicians orient treatment during and after surgery. Methods: Cross-sectional descriptive study design. Collect medical records of 400 patients from October 2023 to February 2024 according to selection criteria (by questionnaire) at Da Nang Women’s and Children’s Hospital. Analyze data using Excel and SPSS 26.0 software. Results: The rate of prostate disorders is 7%, the rate of APTT disorders is 44%, the rate of PT disorders is 6.3% and the rate of fibrinogen disorders is the highest at 81.5%. There is a relationship between hypertension in pregnant women with a decrease of 7%, this difference is statistically significant with p < 0.05. There is a relationship between APTT index and BMI of pregnant women, this difference is statistically significant with p